Degradation of Chlorpyrifos Residue on Tropical Inceptisol Soil with Indigenous Bacteria Treatment - Kurnia, Asep; Zu`amah, Hidayatuz; Sulastri, Baiq Nunung; Makmur, Ria Fauriah (UI Scholars Hub, 2024)
The use of soil microbes is one of the most effective methods for degrading pesticide residue in soil. Microbes can accelerate the degradation of persistent pollutants including chlorpyrifos in soil. This research aims to find soil bacteria with the greatest potential to degrade chlorpyrifos residue in tropical inceptisol soil and determine its degradation index (DI). The soil used in this experiment was collected from agricultural fields in the districts of Demak, Central Java Province, Indonesia. The experiment was performed using factorial randomize complete block design composed of two factors and four replications. The first factors were made up of two treatments, namely, sterile soil (S) and nonsterile soil (NS). The second factors were composed of five treatments, namely, 1) Delftia acidovorans, 2) Entrobacter sp., 3) Chryseobacterium geocarposphaerae, 4) a mix of three bacteria, and 5) without bacteria (check). Results revealed that D. acidovorans grew faster than other bacteria in chlorpyrifos-contaminated soil. The optimum condition of bacteria growth and chlorpyrifos degradation was observed at the temperature of 28.9 ℃ and soil pH of 5.75. D. acidovorans promoted the degradation of chlorpyrifos residue in soil faster than others with a DI of 0.096. The half-life of chlorpyrifos in soil was faster in NS than in S.